State of Alaska - National Geographic Society (U.S.). Cartographic Division (Washington : The Society, 1959)
3 insets: Aleutian Islands, Diomede Islands and Vegetation and land use.
Relief shown by contours and spot heights.
"Atlas plate 18."
Also available online
Keywords: Alaska -- Maps